Instructional design and pilot validation of an interdisciplinary cooperative problem-based learning module for STEM higher education - Mengfan Zhang; Kamisah Osman; Siti Nur Diyana Mahmud (International Journal of Evaluation and Research in Education (IJERE), 2026)
Current instruction in Chinese higher science, technology, engineering, and mathematics (STEM) education often relies on traditional lecture formats, which can limit students’ development in collaborative problem-solving (CPS) and self-efficacy (SE). To address this gap, this study applied the Dick and Carey instructional design model to develop and validate a cooperative problem-based learning (CPBL) module. Structured around an engineering design task, the module integrates cooperative elements into problem-solving workflows and includes mechanisms to support equitable participation, such as mandatory role rotation. A multidisciplinary expert panel (N=6) assessed the module’s content validity, and a pilot study with undergraduate students (N=33) evaluated instructional feasibility and instrument reliability. Results showed high scale-level content validity index (S-CVI=.98) and strong internal consistency for the adapted CPS and SE scales (Cronbach’s α>.80). These findings confirm the module’s validity, feasibility, and reliability. Ultimately, this CPBL module offers a validated pedagogical framework for interdisciplinary STEM instruction to concurrently cultivate the technical and transversal skills required in higher education.